2001
DOI: 10.1111/j.1572-0241.2001.03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an increased nitric oxide production in primary biliary cirrhosis

Abstract: Evidence of an increased nitric oxide production in primary biliary cirrhosis. / Battista S; Bar F; Mengozzi G; Pollet C; Torchio M; Cavalli G; Rosina F; David E; Cutrin JC; Cavalieri B; Poli G; Molino G.. -In: AMERICAN JOURNAL OF GASTROENTEROLOGY. -ISSN 0002-9270. -96(2001), pp. 869-875. Original Citation:Evidence of an increased nitric oxide production in primary biliary cirrhosis. Terms of use:Open Access (Article begins on next page) Anyone can freely access the full text of works made available as "Open A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…The endothelial nitric oxide synthase (eNOS) gene has been previously studied in PBC and has been associated with disease severity rather than disease susceptibility [20,22]. With regard to the eNOS exon7 894G/T polymorphism, contrary to our findings, no association with the disease development was detected although an association of allele T with progressive disease has been detected in that study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The endothelial nitric oxide synthase (eNOS) gene has been previously studied in PBC and has been associated with disease severity rather than disease susceptibility [20,22]. With regard to the eNOS exon7 894G/T polymorphism, contrary to our findings, no association with the disease development was detected although an association of allele T with progressive disease has been detected in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…In experimental animal models, it has been showed that the eNOS enzymatic activity may be markedly affected in liver injury, leading to increased sinusoidal resistance [18,19]. Circulating levels of NO are increased in patients with more severe disease [20], but the relative roles of eNOS and iNOS expression in PBC are still unknown. NO produced from eNOS is clearly beneficial to the liver for its role in maintaining perfusion, and preventing platelet adhesion, thrombosis, and PMN accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of NO in cirrhotic patients is related to the severity of liver damage [19]. Battista et al [9] reported that enhanced NO production in primary biliary cirrhosis could be related to the development of a strong inflammation and at least partially to neutrophil activation. In addition, NO upregulation is dependent on the inflammatory stage of liver cirrhosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been illustrated that nitric oxide (NO) produced through inducible nitric oxide synthase (iNOS) may play an important role in the pathogenesis of bile duct injury in primary biliary cirrhosis [9,10]. However, the role of NO production towards liver fibrosis in BA patients has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of NO in the sera, and increased expression of inducible nitric oxidase synthase (iNOS) at the site of damaged BECs have been reported in PBC. [6][7][8] Indeed, NO may be involved in the pathogenesis of several autoimmune diseases by causing damage to mitochondria and inducing several proinflammatory cytokines. 9 From the therapeutic viewpoint, PBC represents a unique autoimmune disease, because immune suppressive agents are ineffective in PBC, although immune suppressor drugs are widely used, effectively, for other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%